2014
DOI: 10.5603/fm.2014.0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of additional head of biceps brachii: a study with autopsy material

Abstract: Additional head of the biceps brachii (AHBB) has been reported in different po (Folia Morphol 2014; 73, 2: 193-198)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 15 publications
2
26
1
3
Order By: Relevance
“…The incidence of AHBB in this study is located at the upper segment of what has been reported in the literature and could be a morphologic trait of the Colombian population; in agreement with prior studies, the origin was the inferomedial surface of the humerus. 4 Kumar et al reported the presence of third head biceps brachii muscle in 3.33% cases. In their study, they observed a bilateral presence of additional heads and their varied pattern of origin, their insertion was to the tendon of biceps brachii muscle or to its aponeurosis.…”
Section: Resultsmentioning
confidence: 98%
“…The incidence of AHBB in this study is located at the upper segment of what has been reported in the literature and could be a morphologic trait of the Colombian population; in agreement with prior studies, the origin was the inferomedial surface of the humerus. 4 Kumar et al reported the presence of third head biceps brachii muscle in 3.33% cases. In their study, they observed a bilateral presence of additional heads and their varied pattern of origin, their insertion was to the tendon of biceps brachii muscle or to its aponeurosis.…”
Section: Resultsmentioning
confidence: 98%
“…Describen una mayor frecuencia del lado derecho, habiendo encontrado dos casos de bilateralidad (12,5 %). En otro estudio de ese país hecho por Ballesteros et al (2014) con un total de 106 miembros superiores disecados en 53 cadáveres encontraron 21 casos, representando el 19,8 %, sin diferencias en cuanto al sexo y lado. La mayoría se originaba en el segmento inferomedial del cuerpo del húmero.…”
Section: Resultados Y Discusiónunclassified
“…For example, Ansari et al [15] found a case of three-headed BB. However, Ballesteros et al [1] carried out a study in which the results showed that one additional head of the BB is not a rare variant because it occurred in 21% of specimens. Moreover, there are some cases of four-headed BB.…”
Section: Discussionmentioning
confidence: 99%